Probing Classifiers are Unreliable for Concept Removal and Detection - Kumar, Abhinav; Tan, Chenhao; Sharma, Amit (2022 Neural Information Processing Systems, 2022)
Neural network models trained on text data have been found to encode undesired linguistic or sensitive attributes in their representation. Removing such attributes is non-trivial because of a complex relationship between the attribute, text input, and the learnt representation. Recent work has proposed post-hoc and adversarial methods to remove such unwanted attributes from a model's representation. Through an extensive theoretical and empirical analysis, we show that these methods can be counter-productive: they are unable to remove the attributes entirely, and in the worst case may end up destroying all task-relevant features. The reason is the methods' reliance on a probing classifier as a proxy for the attribute. Even under the most favorable conditions when an attribute's features in representation space can alone provide 100% accuracy for learning the probing classifier, we prove that post-hoc or adversarial methods will fail to remove the attribute correctly. These theoretical implications are confirmed by empirical experiments on models trained on synthetic, Multi-NLI, and Twitter datasets. For sensitive applications of attribute removal such as fairness, we recommend caution against using these methods and propose a spuriousness metric to gauge the quality of the final classifier.